International Conference on Cancer Research: Life Sciences-Cancer Research - A. SRINIVASAN, CHIEF PATRON (International Journal of Life Science and Pharma Research, 2020)
The present conference is organized to concentrate Cancer Research in India, with a population close to 1·3 billion, and growing, is epidemiologically interesting and challenging for health-care planners. The conference intends to focus on cancer research, diagnosis and prevention. The conference will be offering a unique gathering in respect to scenario of global challenges. It aims to bring together students, teachers, and researchers working in sciences. The conference is expected to be a platform for the gathering of the ideas for the development of cancer research.